(untitled) (Canberra [A.C.T.], 1987)
Newcastle disease is the major virus disease of poultry in many countries of Southeast Asia. The results reported here will have a direct and immediate benefit to village poultry farmers and commercial enterprises in Asia
Keywords: Newcastle disease vaccine,Newcastle disease; Congresses,Prevention,Congresses